GOVERNMENT AND NON-GOVERNMENT SUPPORTS FOR SMALL AND MEDIUM ENTERPRISES (SMEs) IN INNOVATION ADOPTION: A CASE OF INDONESIA - Kifayah Amar (Spektrum Industri, 2012)
This paper attempts to identify supports provided by Government and non-Government agencies in Indonesia. As highlighted in literatures, the characteristics of SMEs are difference to large organizations in particular on their ability to adopt innovation. Based on this fact, the supports should be appropriate for the need of SMEs. Unfortunately, the current Government programs to strengthening local SMEs are still far from their needs in particular to help in their innovation adoption. Non-Government agencies which mainly supported by foreign donors seems better in their strengthening programs for Indonesian SMEs. For instance, the agencies always carry out the training need analysis in order to deliver the appropriate training program for SMEs. Keywords: innovation, Government support, SME